Application of Ion-Exchange Resin Column for Basic Development of Strontium-90/Yttrium-90 Generator for Preparation of Radiopharmaceutical Therapy - Muchtaridi Muchtaridi; Elvan Kamal; Anas Subarnas; Abdul Mutalib (Universitas Gadjah Mada, 2017)
The aim of this study is to examine the possible use of ion-exchange resin on Dowex AG 50x8 in separating Y-90 from Sr-90 which then could be applied in the basic of manufacture of producing Sr-90/Y-90 generator for the production of radiopharmaceutical cancer therapy. The findings showed that a distributive coefficient of Sr-90 and Y-90 with HCl 6 N solvent showed that distributive coefficient of Sr-90 in cation-exchange resin on Dowex 50x8 was greater than Y-90. Y-90 in HCl 6 N solvent was more easily eluted, while Sr-90 was bound to resin.. In conclusion, resin on Dowex AG 50x8 with HCl 6 N elution solvent might be able to separate Y-90 from Sr-90 as the basis for Sr-90/Y-90 generator.